PENTINGNYA ETIKA DALAM BERBISNIS (Depot Air Minum Isi Ulang Kabupaten Nabire) - Komul, Liza Meichy Eveline (SKETSA : Jurnal Ilmu-Ilmu Sosial, 2018)
Business ethics is the science of what is good and what is bad in doing business. With the ethics of doing business, companies or business people are able to know the rules of values and even the norms in carrying out their business. It was found that the sale of Refill Drinking Water Depots was cheating by did not pay attention to the cleanliness of the water and the gallons used. This was very detrimental to consumers or the community.This writing aims to find out the business people or companies in carrying out business ethics From the results of this study, it is known that there are still many business people who commit fraud in doing business, violating rules, values and norms that must be applied in doing business.